2006
DOI: 10.1002/smi.1094
|View full text |Cite
|
Sign up to set email alerts
|

Associations between physical activity and perceived stress/hassles in college students

Abstract: Physical activity is often recommended as a strategy for managing stress. Although associations among physical activity, stress, and hassles have been documented among adults and children, they have not been studied extensively in college populations. This cross‐sectional study employed an ethnically diverse sample of 814 male and female students from three types of colleges in southern California to examine the relationship between physical activity and two indices of stress. Anonymous paper‐and‐pencil questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
80
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(99 citation statements)
references
References 26 publications
6
80
0
8
Order By: Relevance
“…Partially determined by genetics (He et al, 2009), these inter-individual differences in sleep need may be one reason why stronger associations amongst stress, sleep and health are not evident. It is also likely that some of this variance can be accounted for by behavioural factors; those who are stressed are more likely to smoke (Booker et al, 2008;Ng & Jeffery, 2003), exercise less frequently (Nguyen-Michel, Unger, Hamilton, & Spruijt-Metz, 2006) and have poorer nutritional practices (Roohafza et al, 2007); and sleep duration has also been shown to be associated with smoking, alcohol use and leisure-time physical inactivity (Schoenborn & Adams, 2008). The results of the current study suggest that it may also be critical to distinguish between sleep duration and sleep quality.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…Partially determined by genetics (He et al, 2009), these inter-individual differences in sleep need may be one reason why stronger associations amongst stress, sleep and health are not evident. It is also likely that some of this variance can be accounted for by behavioural factors; those who are stressed are more likely to smoke (Booker et al, 2008;Ng & Jeffery, 2003), exercise less frequently (Nguyen-Michel, Unger, Hamilton, & Spruijt-Metz, 2006) and have poorer nutritional practices (Roohafza et al, 2007); and sleep duration has also been shown to be associated with smoking, alcohol use and leisure-time physical inactivity (Schoenborn & Adams, 2008). The results of the current study suggest that it may also be critical to distinguish between sleep duration and sleep quality.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…To maximise within-subject differences in stress reactivity and to demonstrate the treatment effect, we chose the following two real-life assessment periods: We set the pre-intervention baseline assessment to the beginning of the semester because we assumed that students had low stress at this time. The post-intervention assessment was set to the end of the semester (the examination period) and was used as the real-life stressful episode given that academic examinations are a real-life demand that induces noticeable stress in students (Hazlett, Falkin, Lawhorn, Friedman, & Haynes, 1997;Nguyen-Michel, Unger, Hamilton, & Spruijt-Metz, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…[9] Among college students, previous studies have shown that those who regularly exercise perceive less stress, have less deleterious effect of stress on the heart, exhibited enhanced cardiac recovery after stressful event, and prevented the occurrence of stress-induced immunosuppression. [10,11] Previous studies also showed that although nursing students were aware that exercise is a health-promoting behavior, they were not regularly engaging in physical activities due to the stress of academic demands, and the practice of risky behaviors such as alcohol consumption. [7,[12][13][14] Government and organizational guidelines for healthy exercise performance include at least 30 minutes of moderate-intensity physical activity five days/week or 20 minutes of vigorous activity three days/week.…”
Section: Introductionmentioning
confidence: 99%